Banking Crises : Cases and Issues. (International Monetary Fund, 1991)
The condition of banking systems in developing countries strongly influences the design and effectiveness of economic adjustment policies. Bank portfolio weakness can limit the flexibility of interest rate policy, the scope of financial reforms, and the conduct of monetary and fiscal policy. This volume, edited by V. Sundararajan and Tomas J.T. Balino, is a collection of papers by IMF economists. It examines the link between financial problems and macroeconomic policy and highlights the need for prudential regulations and the appropriate institutional framework to deal with problem banks and borrowers.